PENGGUNAAN INTERNET OLEH DOSEN BERDASAR GENDER DAN GENERASI - Rina Sari Kusuma (Universitas Muhammadiyah Surakarta, 2016)
The usage of internet in higher education is increasing. This system is beingimplemented for efficiency and effectivity of communication and activity monitoring among the academicians. On the other hand, not all academicians have the exact same technology literacy. Muhammadiyah University of Surakarta is one of top university in Indonesia that already use many internet based programmes in their academic and administration activities. The purpose of this research see how the role of gender and generation affect the internet usage of academicians in UMS. Internet usage pattern covers items such as knowledge and experience on the internet, purpose of using internet, and frequency of using e-mail. The result shows that generation become the main factor that influence the pattern and optimalization usage of the internet than the gender one. Academicians that belong to Generation Y or milineal is the generation that has the highest potential of maximalize the internet technology, especially for academic activity.